From Retail to Pre-Tail & E-Tail: Evolution of E-Commerce in India (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Today online retail represents a small fraction of the e-Commerce space  but it is one of the fastest growing segments in India; only in 2012 online  shopping e-Commerce site number has crossed 600 from 100. India is  at the verge of a big digital revolution. Declining prices of broadband  subscription, aided by the launch of 3G services and the likely launch of  4G services is expected to significantly add up to the country’s internet  user base. Because of India’s rising internet population, the trend of on line shopping is set to see greater heights in coming years. Furthermore,  the Indian consumer’s perception of online shopping has undergone a  drastic change, and only for the good. In this paper, we discuss Pre-tail ing: the need of the hour. Also the factors which are driving online retail  consumption in India. We also talk about the popular trends in the online  retail industry and analyze other factors contributing to the growth of  e-Commerce in India.
Keywords: E-Commerce; E-Tail; Online Retail; Online Shopping; Pre-Tail